Synthesis of monophosphorylated lipid A precursors using 2-naphthylmethyl ether as a protecting group - Xue, Jundi; Han, Ziyi; Li, Gen; Emmanuel, Khalisha A.; McManus, Cynthia L.; Sui, Qiang; Ge, Dongmian; Gao, Qi; Cai, Li (Beilstein Journal of Organic Chemistry, 2020)
Lipid A, the hydrophobic domain of lipopolysaccharide (LPS), is a strong immunostimulator and therefore a valuable target for the development of novel immunomodulators. Various lipid A derivatives have been chemically synthesized in order to reduce toxicity while retaining the immunostimulatory activity. In this work, we describe a novel approach to the frequently problematic synthesis of monophosphorylated mono- and disaccharide lipid X using a combination of established chemistry and a novel 2-naphthylmethyl ether (Nap) protecting group for “permanent” protection of hydroxy groups. Of particular note is the fact that the key Nap protecting group is able to remain in the molecule until the final global deprotection step. Our synthetic strategy is not only efficient in regards to the yield of the various chemical transformations, but also robust in regards to the potential application of this route to the production of other lipid A analogs.
Keywords: lipid A; lipid X; lipopolysaccharide; 2-naphthylmethyl ether; synthesis